Investasi Vs Judi Online: Kenali Perbedaannya dan Hindari Bahayanya - Eri Kusnanto; Nabila Hilyatunisa; M. Reza Saputra; Santa Kristina Sese; M. Farel Deniyu (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to identify the fundamental differences between investment and online gambling, as well as their impacts on society. The method employed is a qualitative approach with descriptive analysis through interviews with financial experts and surveys of the public to measure their understanding of both activities. The results indicate that many individuals still perceive investment as a form of gambling despite the fact that they possess distinct characteristics; investment is conducted based on analysis and long-term strategies, while online gambling is speculative and high-risk in nature. The conclusion of this study emphasizes the importance of financial literacy education in enhancing public understanding and preventing financial losses due to online gambling practices.